2014
DOI: 10.1149/2.028408jes
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a Full Layer Pore-Scale Model for the Simulation of Electro-Active Material Used in Power Sources

Abstract: A general pore-scale model was developed which mimics the electro-active layer formation process. The model was used to simulate the active material loading on battery, fuel cell and supercapacitor electrodes. The active layer was reconstructed by coating 10 8 particles with different interparticle interactions onto a smooth surface. Instead of simulating each generated layers at macro scale, scaling analysis was applied to reduce the complexity of the system. It was shown, that the generated layers belong to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Kriston et al developed a pore-scale model accompanied by a stochastic method to mimic the electroactive layer formation process in energy storage devices, and they employed a scaling analysis to reduce the complexity of the system. 57 Their work demonstrated that the interparticle interaction and material loading affected the morphological properties of electroactive layer. However, their work did not consider multiphase interaction which is important in electrode preparation.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…Kriston et al developed a pore-scale model accompanied by a stochastic method to mimic the electroactive layer formation process in energy storage devices, and they employed a scaling analysis to reduce the complexity of the system. 57 Their work demonstrated that the interparticle interaction and material loading affected the morphological properties of electroactive layer. However, their work did not consider multiphase interaction which is important in electrode preparation.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…The activated carbon support (ACCS) was prepared using the procedure developed in the Center for Electrochemical Engineering at University of South Carolina (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The Pt/ACCS was synthesized using a modified polyol method (7,9,11).…”
Section: Synthesis Of Activated Carbon Composite Support and Compress...mentioning
confidence: 99%
“…Compressive platinum lattice catalyst (Pt*/ACCS) was prepared using a methodologies developed at USC (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The amount of Co used as a doping material targeted different atomic ratio of PtCo in Pt*/ACCS catalyst.…”
Section: Development Of Ultra-low Highly Active and Durable Hybrid Co...mentioning
confidence: 99%